The food crisis and the price of agricultural products (Research, Society and Development, 2020)
We are witnessing the national and international debate about the production of food and agrofuels, which has been showing a fragility of the agrifood system in world crises. Existing crises go through the coexistence of three major crises: financial, energy and, mainly, food. Rising food prices over the past few years have raised concerns about the food and nutritional situation of people in developing countries and widespread inflation, where they have driven millions of people to food insecurity. The study was based on bibliographic research of articles and journals indexed in electronic databases to list the reasons for the food crisis, the high prices of agricultural products and the demand for food, with an emphasis on energy crops in a global context. Recent economic growth has been the main driver of the reduction of poverty and hunger in the world. The rise in food prices can aggravate the situation of hunger in the world, reducing the purchasing power, especially of the urban poor and low-income countries with a food deficit, so that energy foods can help to alleviate this situation.